Literatura, comunismo e campesinato: uma leitura de Bernardo Élis - Pauliane de Carvalho Braga (2015)
In this work we will seek to understand the political rise of the Brazilian peasantry and the mediation conducted by the Brazilian Communist Party (PCB) in this process, from Bernardo Élis work, a writer borned in Goiás, Brazil. Analyzing his work between 1944 and 1966 (Ermos e Gerais, A terra e as carabinas, O tronco, Veranico de Janeiro e Caminhos e descaminhos) we seek to understand in what extent the author intervened in the political debate of the period. Telling the story of a Republic that was built far from what was common, literarily recreating the stress points and the anchorage of social and power relations established in the hinterlands, and pointing out the undone in the Brazilian political project, Bernardo Élis established the limit of a world that could no longer exist. His literary contribution to the debate about the Brazilian peasantry is relevant not only to put that issue on the political agenda, but to qualify it, humanizing their characters. Élis built images and particular points of view for the peasants and settlers shown in his work, as well as the land owners, Coronéis, judges, and the police forces. Putting together history, politics and fiction, the author has built a system of ideas that underlined possibilities, offering his particular view of life, and showing the possibility of political integration to the actors that lies outside de mainstream history subjects.